2016
DOI: 10.1051/0004-6361/201527063
|View full text |Cite
|
Sign up to set email alerts
|

Disk galaxy scaling relations at intermediate redshifts

Abstract: Aims. Galaxy scaling relations such as the Tully-Fisher relation (between the maximum rotation velocity V max and luminosity) and the velocity-size relation (between V max and the disk scale length) are powerful tools to quantify the evolution of disk galaxies with cosmic time. Methods. We took spatially resolved slit spectra of 261 field disk galaxies at redshifts up to z ≈ 1 using the FORS instruments of the ESO Very Large Telescope. The targets were selected from the FORS Deep Field and William Herschel Dee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(50 citation statements)
references
References 68 publications
10
40
0
Order By: Relevance
“…In all these data sets we note that V max and M B were computed using the same methods presented in this study, which makes them ideal for a direct comparison. The scatter of our cluster sample at z∼0.45 is consistent with what has been previously found in the field (Böhm & Ziegler 2016), while the reported offset in B-band luminosity is larger than that of the Bösch et al (2013b) sample at lower redshift, but in line with what has been found by previous observational studies (Bamford et al 2005) and predictions from semianalytical models (Dutton et al 2011). We repeated our analysis for the M * -TFR ( Fig.…”
Section: The Tully-fisher Relationsupporting
confidence: 92%
See 1 more Smart Citation
“…In all these data sets we note that V max and M B were computed using the same methods presented in this study, which makes them ideal for a direct comparison. The scatter of our cluster sample at z∼0.45 is consistent with what has been previously found in the field (Böhm & Ziegler 2016), while the reported offset in B-band luminosity is larger than that of the Bösch et al (2013b) sample at lower redshift, but in line with what has been found by previous observational studies (Bamford et al 2005) and predictions from semianalytical models (Dutton et al 2011). We repeated our analysis for the M * -TFR ( Fig.…”
Section: The Tully-fisher Relationsupporting
confidence: 92%
“…Black circles represent cluster galaxies at z∼0.2 fromBösch et al (2013b). The solid black line shows the local B-band TFR(Tully et al (1998)) with a 3σ scatter area around reported byBöhm & Ziegler (2016) for galaxies at 0<z<1 (gray area). The orange, blue, and black dashed lines represent the best fit for the cluster and field sample of this study and the cluster sample fromBösch et al (2013b), respectively.…”
mentioning
confidence: 96%
“…This evolution is explained by the rise of SFR and the gradual evolution of SP with lookback time. A simple extrapolation of the luminosity evolution linear fit given by Böhm & Ziegler (2016) (gray line) shows that ∆M B = −1.2 ± 0.4 magnitudes at z=1.4. As explained in Figure 3A, our cluster sample can be divided into two groups by their total mass.…”
Section: Resultsmentioning
confidence: 99%
“…A very important quantitative tool in case of spiral galaxies is the Tully-Fisher relation (TFR), which combines the luminosity of the stellar population (SP) with the characteristic rotational velocity taken as proxy for the total mass (including dark matter). It is well established in the local Universe (Pierce & Tully 1992) and was examined for evolution in recent years out to redshift 1, including work by our own group (Ziegler et al 2003, Böhm et al 2004, Böhm & Ziegler 2007and Böhm & Ziegler 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Hα-based star formation rates versus offsets ∆ M B from the local B-band Tully-Fisher relation. In contrast to field disk galaxies at z < 1 (small open squares; taken fromBöhm & Ziegler 2016), the TFR offsets of the z = 1.47 (proto-)cluster galaxies (filled circles) are not correlated with star formation rate. See text for details.…”
mentioning
confidence: 97%